BIOASSESSMENT MENGGUNAKAN MAKROINVERTEBRATA BENTIK UNTUK PENENTUAN KUALITAS AIR SUNGAI CITARUM HULU - Barti Setiani Muntalif (Purifikasi, 2008)
The aims of this research were to evaluate the potential of benthic macroinvertebrates community assemblages in predicting the river water quality status. Eight sampling station with various quality riparian were selected at the upper Citarum River in West Java, in order to determine changes in the benthic macroinvertebrates community associated with variability in water quality. Analysis of potensial water pollution sources in assess the status of water quality in based on Physical-Chemical Index and three metrics biology of benthic macroinvertebrate to be correlated. The results showed that the water quality of upper Citarum River decreased as the river flew downstream into traditional dairy farm, urban area, and industrial area. Based on correlation test, the highest coefficient value was shown by Lincoln Quality Index (LQI) (r = 0,97) compared to Family Biotic Index (FBI) (r = 0,89), and Diversity Index (DI) (r = 0,79).